The spin-reorientation magnetic transitions in Ga-doped SmCrO3. Issue 15 (15th October 2018) - Li, H.; Liu, Y.Z.; Xie, L.; Guo, Y.Y.; Ma, Z.J.; Li, Y.T.; He, X.M.; Liu, L.Q.; Zhang, H.G.
Abstract: Orthochromite SmCrO3 is known to show spin reorientation around 34 K and which was assigned as transition from Γ 4 to Γ 2 . Our work reports the spin reorientation transitions in a series of Ga-doped SmCrO3 : the spin reorientation transition from Γ 4 to Γ 2 at T SR2 = 88 K and another spin reorientation transition of Γ 2 to Γ 1 at T SR1 = 15 K were observed simultaneously when the content of Ga is 30%. Importantly, the evolution of spin reorientation transitions from the single spin reorientation of Γ 4 → Γ 2 to double ones of Γ 4 → Γ 2 → Γ 1, and then to the single one of Γ 2 → Γ 1 is caused by the increase of Ga doping concentration. The M - T and M - H measurements have been made to study the temperature and magnetic field dependence of these spin reorientation transitions. These temperatures and doping dependence of spin reorientation transitions in RCrO3 ( R = rare earth or yttrium) can appeal to the magnetic switching devices design based on these findings.